Improving the low voltage ride through of doubly fed induction generator during intermittent voltage source converter faults - Abdou, A.; Abu-Siada, Ahmed; Pota, H. (AIP Publishing LLC, 2013)
The impact of different voltage source converter (VSC) faults on the low voltage ride through (LVRT) capability of the doubly fed induction generator (DFIG) is also investigated. Faults such as fire-through of the VSC switches and short circuit across the DC-link capacitor are considered in this paper. The impact of internal VSC faults when they occur within the grid side converter (GSC), and rotor side converter is investigated. A proper static synchronous compensator (STATCOM) controller to mitigate the effects of these faults is proposed. The DFIG compliance with numerous and recently released LVRT grid codes under these faults, with and without the STATCOM, is examined and compared. Simulation results indicate that these types of faults have a severe impact on the DFIG voltage profile, especially when these faults occur in the GSC. This is attributed to the fact that the GSC directly regulates the point of common coupling (PCC) voltage. Moreover, the proposed controller is capable of bringing the voltage profile at the PCC to the nominal steady state level and hence maintaining the connection of the wind turbine during the various studied faults.